Determinasi Harga Saham Perusahaan Manufaktur Subsektor Makanan dan Minuman - Zuhri, Saefudin; Juhandi, Nendi; Sudibyo, Heru Harmadi; Fahlevi, Mochammad (AGUSPATI Research Institute, 2020)
This study aims to analyze the effect of return on assets (ROA), net profit margin (NPM), and debt to equity ratio (DER) on stock prices. The study was conducted on the food and beverage sub-sector listed on the Indonesia Stock Exchange in the period 2013-2017. The samples used in this study were 12 companies, while the data collection method used written documentation with the sampling technique using purposive sampling. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used in this study is multiple regression analysis, using the SPSS version 25 method. The results of the study showed that return on assets (ROA) had no significant effect on stock prices. Net profit margin (NPM) has a significant effect on stock prices. Debt to quity ratio (DER) no significant effect on stock prices and simultaneous return on assets (ROA), net profit margin (NPM) and debt to equity ratio (DER) have a significant effect on stock prices by 19.4%.